Semantic Analysis of the Sinjab Language in Relation to the Javanese Language in Batang - R. Ndaru Bagus Prasetyo (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2026)
The Sinjab language is a local slang variety spoken in Batang that reflects the cultural and social identity, as well as the creativity, of the local community. However, it currently faces the risk of extinction due to a lack of documentation and intergenerational transmission. This study aims to identify how the Sinjab language is used in the daily routines of the Batang community and to analyze the semantic meanings of Sinjab vocabulary in Javanese. This study employs a descriptive qualitative method using participatory observation, interviews, and documentation with active speakers of the Sinjab language. Data were obtained from primary sources through direct interaction within the community as well as from secondary sources such as YouTube videos and posts by local communities. The research findings indicate that the Sinjab language possesses a unique lexical structure through word-formation processes such as metathesis, phoneme addition, and borrowing elements from other languages. Sinjab vocabulary exhibits semantic relationships—such as synonymy, antonymy, metaphor, and idiomatic expressions—that are not found in Standard Javanese. Furthermore, observations reveal a significant decline in its use, which is now limited to specific social groups, such as punks or marginalized individuals. This study underscores that documenting and revitalizing the Sinjab language are essential to preserving the continuity of this nearly extinct regional cultural heritage.